Thermo-fluid Dynamics of Two-Phase Flow - Ishii, Mamoru; Hibiki, Takashi (Springer US : Imprint: Springer, 2006)
Thermo-fluid dynamics of two-phase flow is an important subject for various scientific and engineering fields. It plays a particularly significant role in thermal-hydraulic analysis of nuclear reactor transients and accidents. The topics of multiphase flow are also essential for various engineering systems related to energy, chemical engineering processes and heat transfer. Thermo-fluid Dynamics of Two-phase Flow is written for graduate students, scientists and engineers who need in depth theoretical foundations to solve two-phase problems in various technological systems. Based on the extensive research experiences focused on the fundamental physics of two-phase flow, the authors present the detailed theoretical foundation of multi-phase flow thermo-fluid dynamics as they apply to: - Nuclear reactor transient and accident analysis - Energy systems - Power generation systems - Chemical reactors and process systems - Space propulsion - Transport processes.